2020
DOI: 10.1891/2380-9418.jdnp-d-19-00030
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Education Program to Improve Nurses' Knowledge and Confidence on Delirium Recognition in a Surgical-Trauma Intermediate-Care Setting

Abstract: BackgroundHigh incidence of delirium in hospitalized patients has been reported in the United States and is significantly associated with increased morbidity and mortality. The lack of knowledge and confidence in performing delirium assessment (KCDA) has led to significant underrecognition of delirium by nurses regardless of evidence-based education intervention.ObjectiveThe purpose of this study was to determine the effectiveness of a multimodal educational program (MEP) to enhance nurses' KCDA.MethodsA MEP i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The current study revealed that delirium care knowledge, confi- combining video simulation and one-on-one bedside coaching with delirium screening was effective (Choi et al, 2020). By adopting a similar approach in our study, we confirmed the effectiveness of implementing a simulation-based education programme in an ICU.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The current study revealed that delirium care knowledge, confi- combining video simulation and one-on-one bedside coaching with delirium screening was effective (Choi et al, 2020). By adopting a similar approach in our study, we confirmed the effectiveness of implementing a simulation-based education programme in an ICU.…”
Section: Discussionsupporting
confidence: 75%
“…As the aforementioned literature suggested, simulation‐based education programmes are expected to be effective, and delirium knowledge, confidence and competence are sustained over time after completing simulation‐based education programmes. In particular, a recent quasi‐experimental trial utilized a multimodal delirium care education programme to improve the delirium care knowledge and confidence of surgical nurses, demonstrating that combining video simulation and one‐on‐one bedside coaching with delirium screening was effective (Choi et al, 2020). By adopting a similar approach in our study, we confirmed the effectiveness of implementing a simulation‐based education programme in an ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation